2014
DOI: 10.1556/imas.6.2014.3.1
|View full text |Cite
|
Sign up to set email alerts
|

Transradial access for renal artery intervention

Abstract: Abstract:Introduction: Percutaneous interventional procedures in the renal arteries are usually performed using a femoral or brachial vascular access. The transradial approach is becoming more popular for peripheral interventions, but limited data exists for renal artery angioplasty and stenting. Methods: We have analyzed the clinical, angiographic and technical results of renal artery stenting performed from radial artery access between 2012 and 2013. The radial artery anatomy was identifi ed with aortography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
0
12
0
2
Order By: Relevance
“…According to our knowledge, there are only a few hospitals where radial access is regularly performed for interventions in the systemic circulation. Most of the related publications report the use of radial access for cerebral angiograms and carotid artery stenting (16,17) and only a few report procedures below the diaphragm (11)(12)(13)(14)(15). Only three groups reported abdominal or pelvic visceral interventions in the English literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to our knowledge, there are only a few hospitals where radial access is regularly performed for interventions in the systemic circulation. Most of the related publications report the use of radial access for cerebral angiograms and carotid artery stenting (16,17) and only a few report procedures below the diaphragm (11)(12)(13)(14)(15). Only three groups reported abdominal or pelvic visceral interventions in the English literature.…”
Section: Discussionmentioning
confidence: 99%
“…Only three groups reported abdominal or pelvic visceral interventions in the English literature. A group at Tokyo Women's Medical University Daini Hospital (Tokyo, Japan) reported that they performed abdominal interventions in 426 patients between 2000 and 2004 via the transradial approach, including 177 cases of transarterial hepatic chemoemboli-zations (15,22); Ruzsa et al (14) reported renal artery angioplasty and stenting in 27 patients; Resnick et al (13) reported uterine artery embolization in 29 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this shift in access site preference among interventional cardiologists, TFA remains the predominant access site choice for peripheral and visceral interventions. Literature examining the feasibility of TRA for noncoronary interventions is relatively sparse, although its safety and feasibility have been described for uterine artery embolization (8), renal artery intervention (9), and transarterial chemoembolization (10). In a 2003 study by Shiozawa et al (10), overall access site complications were found to be significantly less in TRA versus TFA in treating hepatocellular carcinoma via transarterial chemoembolization (4.5% vs 12.7%), while maintaining comparable therapeutic efficacy.…”
Section: Abbreviationsmentioning
confidence: 99%
“…There is a paucity of data in the literature describing renal artery interventions through radial site access [ 11 ]. To the best of our knowledge, this is the first case illustrating the novel technique of percutaneous transluminal balloon angioplasty and DES placement with the assistance of GL through radial access in the complex ISR of the renal artery.…”
Section: Discussionmentioning
confidence: 99%